Where is the glueball? - Krupa, D. (Array, 2008)
Summary: The processes pp®pp, K[`K] and hh, with IGJPC = 0+0++, are analysed by means of simultaneous coupled-channel analysis of all available data. The investigation is focussed on the properties of the f0(665), f0(980), f0(1370), f0(1500) and f0(1710) states with the aim to determine their quark-gluonic content. The analysis supports the existence of f0(665) as a very broad resonance. It suggests further to see the f0(980) state as predominantly the hh bound state. The quark content of other states is inferred and f0(1500) appears as a mixed state with dominant glueball component